2018
DOI: 10.2147/ijwh.s158621
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experiences with postpartum anxiety disorders: a narrative literature review

Abstract: PurposePostpartum anxiety disorders are common and may have significant consequences for mothers and their children. This review examines the literature on women’s experiences with postpartum generalized anxiety disorder (GAD), postpartum panic disorder (PD), obsessive compulsive disorder (OCD), and posttraumatic stress disorder (PTSD).MethodsMEDLINE (Ovid), CINAHL, PsycINFO, and reference lists were searched. Qualitative and quantitative studies assessing women’s experiences with GAD, postpartum PD, OCD, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 36 publications
2
36
0
3
Order By: Relevance
“…Similarly, in relation to the S-BSS-R SE sub-scale women experiencing an unassisted delivery scored significantly higher compared to those receiving an intervention, thus, and again consistent with other studies (Fleming et al, 2016;Hollins Martin and Martin, 2014;Jefford et al, 2018), indicating that assisted delivery is associated with less satisfaction and more stress. Given the relationship of stress as a fundamental component to distinct perinatal mental health presentations, ranging from postpartum posttraumatic stress disorder (Ali, 2018;Dikmen-Yildiz et al, 2017;Shlomi Polachek et al, 2016), tokophobia (Goutaudier et al, 2018;Striebich et al, 2018) and postnatal depression (Dennis et al, 2018;Pampaka et al, 2018), this finding yields valuable data regarding the potential implications of delivery type on psychological well-being and the development of psychiatric disturbance. Focusing upon the S-BSS-R QC sub-scale we noted that women who had an assisted delivery were significantly less satisfied in terms of quality of care received compared to those who had an unassisted delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in relation to the S-BSS-R SE sub-scale women experiencing an unassisted delivery scored significantly higher compared to those receiving an intervention, thus, and again consistent with other studies (Fleming et al, 2016;Hollins Martin and Martin, 2014;Jefford et al, 2018), indicating that assisted delivery is associated with less satisfaction and more stress. Given the relationship of stress as a fundamental component to distinct perinatal mental health presentations, ranging from postpartum posttraumatic stress disorder (Ali, 2018;Dikmen-Yildiz et al, 2017;Shlomi Polachek et al, 2016), tokophobia (Goutaudier et al, 2018;Striebich et al, 2018) and postnatal depression (Dennis et al, 2018;Pampaka et al, 2018), this finding yields valuable data regarding the potential implications of delivery type on psychological well-being and the development of psychiatric disturbance. Focusing upon the S-BSS-R QC sub-scale we noted that women who had an assisted delivery were significantly less satisfied in terms of quality of care received compared to those who had an unassisted delivery.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of women’s health, anxiety and depression symptoms are common in the postpartum period [1]. A recent literature review reported that generalized anxiety disorder, PD, obsessive compulsive disorder (OCD), and post-traumatic stress disorder are frequently diagnosed in postpartum women [2]. Specifically, the prevalence of clinically significant anxiety and depression, which is the most common mental condition during the postpartum period, has been observed at a rate of 10–20% in developed countries and approximately 30% in developing countries [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of CBT are understudied. CBT’s previous research on perinatal depression and on effectiveness of psychotherapy for non-perinatal adult PD by the rigid systematic review has important implications for perinatal PD [2, 16]. The recent review by meta-analysis including 20 RCTs, including 3623 women, show that CBT as psychotherapy significant improved depression symptoms [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is unsurprising that maternal mental health issues, such as depression and anxiety, are commonly experienced by women during this time. The experience of poor maternal mental health has been associated with a myriad of adverse pregnancy and birth outcomes such as preterm birth 3,[5][6][7] and low infant birthweight 3,6 , in addition to longer-term negative impacts regarding child development [8][9][10][11] , offspring mental health 8,12,13 , early mother-child interaction [14][15][16][17] , and ongoing mental health issues for the mother 17,18 . Despite significant consequences, maternal mental health symptomology continues to be under-recognised and under-treated 2,19 .…”
mentioning
confidence: 99%